2018
DOI: 10.1097/md.0000000000010518
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vessel curvature on neointimal healing after stent implantation as assessed by optical coherence tomography

Abstract: Purpose:Previous studies have indicated that stent implantation could alter the vessel geometry, which may impact the neointimal healing process. Curvature is an important parameter for evaluating vessel geometry. The purpose of our study was to investigate the relationship between vessel curvature and neointimal healing after stent implantation.Methods:Fifty-nine patients with acute coronary syndrome (ACS) who underwent stent implantation were enrolled in the study. According to the post-percutaneous coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…A previous study has reported that irregular protrusion post DES implantation was associated with subsequent heterogeneous neointima at 8‐month follow‐up . Higher vessel curvature after stent implantation may also have an potential impact on the neointimal healing with a higher incidence of heterogeneous neointima . Recent evidences suggested that age, blood lipid level, PCI for ACS, history of cerebrovascular disease and time interval to OCT follow‐up were independent determinants for heterogeneous in‐stent proliferation .…”
Section: Discussionmentioning
confidence: 97%
“…A previous study has reported that irregular protrusion post DES implantation was associated with subsequent heterogeneous neointima at 8‐month follow‐up . Higher vessel curvature after stent implantation may also have an potential impact on the neointimal healing with a higher incidence of heterogeneous neointima . Recent evidences suggested that age, blood lipid level, PCI for ACS, history of cerebrovascular disease and time interval to OCT follow‐up were independent determinants for heterogeneous in‐stent proliferation .…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9] Our study also suggests that this straightening phenomenon goes on after deployment, because follow-up angles were significantly superior to immediate postdeployment angles. 4 In addition to its effects on the incident angle of blood flow into the aneurysm sac, this straightening effect could improve aneurysm occlusion through other mechanisms: It might influence the wall apposition of the flow-diverter stents, 10 and it could also improve the "scaffolding" effect for reconstruction of the aneurysmal neck 11 and promote arterial remodeling in a more favorable geometric configuration. It is, nonetheless, hypothesized that despite the flow-diverting effect, flow-diverter stents inducing important parent artery straightening may, in part, correct the geometric configuration that was involved in aneurysm development in the first place.…”
Section: Discussionmentioning
confidence: 99%